Histochemical characterization of bone and cementum using modified gallego's iron fuschin stain and van gieson stain and its application in fibro-osseous lesions - Ruchika Sanket Agrawal; Jyoti D Bhavthankar; Mandakini S Mandale; Arush Thakur; Priya A Bhagde; Seema Salve (Wolters Kluwer Medknow Publications, 2020)
Objectives: Fibro-osseous lesions (FOLs) of the jaws exhibit an overlapping histomorphologic spectrum with respect to nature of calcifications. Sometimes these calcifications may be difficult to characterize as bone and cementum on routine Hematoxylin and Eosin (H&E) staining. This causes difficulty in assessing the origin and diagnosis of these lesions. Thus the study aimed to characterize bone, cementum, and hard tissue components in FOLs using special stains. Method: The study included a histochemical evaluation of 20 samples of bone and cementum and 12 cases each of fibrous dysplasia (FD) and ossifying fibroma (OF). Three consecutive sections of each tissue were stained with H and E, modified Gallego's iron fuschin stain and Van Gieson stain. H and E and modified Gallego's iron fuschin stained sections were analyzed under light microscope whereas Van Gieson stained section was analyzed under polarizing microscope. Results: It was found that cementum stained red and bone stained greenish-yellow in color. The calcifications seen in fibrous dysplasia stained greenish-yellow in color. Three cases of OF showed greenish-yellow calcifications and nine cases showed reddish calcifications. Polarization study of bone showed lamellar pattern and tooth cementum showed quilt pattern. Four cases of FD showed lamellar pattern and eight cases showed haphazard pattern. In OF, three cases showed lamellar pattern and nine cases quilt pattern. Conclusion: Calcifications having lamellar pattern and greenish-yellow color suggest their osteogenic origin thus having aggressive nature and requiring aggressive treatment. Calcifications having quilt pattern and reddish color suggest periodontal ligament origin thus having less aggressive behavior and less extensive treatment.